2013
DOI: 10.1007/s12350-012-9634-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced administered activity, reduced acquisition time, and preserved image quality for the new CZT camera

Abstract: Reduced administered activity, reduced acquisition time, and preserved image quality for the new CZT camera. Link to publication Citation for published version (APA): Oddstig, J., Hedeer, F., Jögi, J., Carlsson, M., Hindorf, C., & Engblom, H. (2013). Reduced administered activity, reduced acquisition time, and preserved image quality for the new CZT camera. Journal of Nuclear Cardiology, 20(1), 38-44. DOI: 10.1007/s12350-012-9634-6 General rights Copyright and moral rights for the publications made accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 17 publications
(25 reference statements)
0
28
0
Order By: Relevance
“…Based on their prior study of a low-dose protocol for nonobese patients using 2.5 MBq/kg body weight, they projected this concept for patients who were obese in an attempt to expand the 2.5 MBq/kg to all types of patients. 20 In this prospective study, patients weighing less than 110 kg received 2.5 MBq/kg of 99Tc-tetrofosmin, while for patients weighing 110 to 120 kg and [120 kg, a fixed dose of 430 and 570 MBq, respectively, were used. Images were obtained using a conventional gamma camera with resolution recovery software or a newer CZT cameras, with about half of the subjects imaged in each of the two groups.…”
mentioning
confidence: 99%
“…Based on their prior study of a low-dose protocol for nonobese patients using 2.5 MBq/kg body weight, they projected this concept for patients who were obese in an attempt to expand the 2.5 MBq/kg to all types of patients. 20 In this prospective study, patients weighing less than 110 kg received 2.5 MBq/kg of 99Tc-tetrofosmin, while for patients weighing 110 to 120 kg and [120 kg, a fixed dose of 430 and 570 MBq, respectively, were used. Images were obtained using a conventional gamma camera with resolution recovery software or a newer CZT cameras, with about half of the subjects imaged in each of the two groups.…”
mentioning
confidence: 99%
“…As longer scan times were used in the PLAP group, this automatically lowered the required activity. 15 We therefore did not only compare the administered activity between both protocols but also the PAST, as this metric accounts for changes in both activity and scan time. Patients in the PLAP group received a 25% lower PAST during stress MPI.…”
Section: Patient Preparation and Image Acquisitionmentioning
confidence: 99%
“…7,8 Furthermore, a new generation of reconstruction methods for the conventional gamma cameras was recently introduced referred to as Ordered Subset Expectation Maximization with depth-dependent Resolution Recovery (OSEM-RR). 9 Both CZT detectors and OSEM-RR can be used to reduce the radiation exposure to nonobese patients [10][11][12] in accordance with ALARA (As Low As Reasonably Achievable). 13 A large body size may cause a higher proportion of emitted photons being attenuated and scattered within the patient resulting in reduced number of primary photons reaching the detector.…”
mentioning
confidence: 99%
“…12 Other studies have also demonstrated the possibility of low-dose protocol using new CZT technology or new generation of reconstruction algorithms OSEM-RR on conventional gamma cameras in nonobese patients. [16][17][18][19][20] A recent study indicates the possibility of dose reduction also for obese patients with a fixed activity using the CZT technology.…”
mentioning
confidence: 99%